Makna Motivasi Islam Dalam Pemilihan Profesi Sebagai Karyawan Bank Syariah Jatim Surabaya (Telaah Kritis Dalam Perspektif Fenomenologi) - Faizah, Siti Inayatul (Jurnal Ekonomi dan Bisnis Islam, 2015)
This research aims to study the meaning of motivation on how Islam in elections as an employee of Jatim Syariah Bank Surabaya in the critical study of the perspective of Phenomenology. The research method used is the method of qualitative perspective of Phenomenology. The results showed that Motivation has a meaning and a very decisive role for each employee in performing work activities such as the direction of the Organizations work. Fulfillment of necessities of life employees become main factors stemming from internal to themselves as encouragement to work in East Java of Islamic Banks, while the rotation work placements as main external factors that make each employee perform work that could encourage a variety of other expectations such as succession, as well as various allowances in their future. The meaning of motivation that already externalized in various forms of performance that could bring increased and progress for the organization of the company.Â Keyword: Islamic Motivation, Employee, Fenomenology